Simultaneous Downregulation of MTHFR and COMT in Switchgrass Affects Plant Performance and Induces Lesion-Mimic Cell Death - Liu, Sijia; Fu, Chunxiang; Gou, Jiqing; Sun, Liang; Huhman, David; Zhang, Yunwei; Wang, Zeng-Yu (Frontiers in Plant Science, 2017)
Switchgrass (Panicum virgatum) has been developed into a model lignocellulosic bioenergy crop. Downregulation of caffeic acid O-methyltransferase (COMT), a key enzyme in lignin biosynthesis, has been shown to alter lignification and increase biofuel yield in switchgrass. Methylenetetrahydrofolate reductase (MTHFR) mediates C1 metabolism and provides methyl units consumed by COMT. It was predicted that co-silencing of MTHFR and COMT would impact lignification even more than either of the single genes. However, our results showed that strong downregulation of MTHFR in a COMT-deficient background led to altered plant growth and development, but no significant change in lignin content or composition was found when compared with COMT plants. Another unexpected finding was that the double MTHFR/COMT downregulated plants showed a novel lesion-mimic leaf phenotype. Molecular analyses revealed that the lesion-mimic phenotype was caused by the synergistic effect of MTHFR and COMT genes, with MTHFR playing a predominant role. Microarray analysis showed significant induction of genes related to oxidative and defense responses. The results demonstrated the lack of additive effects of MTHFR and COMT on lignification. Furthermore, this research revealed an unexpected role of the two genes in the modulation of lesion-mimic cell death as well as their synergistic effects on agronomic performance.